Korupsi, Kolusi dan Nepotisme (KKN) dalam Perspektif Hadis - Sidik, Hasbi (Tasamuh: Jurnal Studi Islam, 2019)
Corruption is a social phenomenon has existed since the era of the history of Egyptian, Babylonian, Hebrew, Indian, Chinese, Greek, and Ancient Rome. Corruption on the surface appear as a problem. From start to tarap simple to the very modern. Various efforts have been made, law enforcement officials made various efforts to be able to cope. But along with the development of time corruption growing. Including Indonesia Corruption in our country and the day rather than getting lost, it became increasingly greater amounts and fantastic, with the number of players who more and more and congregation. Where did it from starting low-level employees to senior officials, civilian and military officials. This is an emergency that must be taken seriously. Because corruption is so diverse. If not immediately anticipated it will take effect very broad. Corruption occurs in almost all of developing countries including Indonesia besides Nigeria, Peru and the Philippines. A new issue currently developing is that corruption is related to the other organized crimes especially to the attempt of corruptors to hide their corruption-originated income through money laundering by using derivative transaction through an effective international transfer. Meanwhile, according to the data found by Asian Development Bank in Perceived Standard, it is stated that Indonesia belongs to the first place in cost competitiveness if compared to the other Asian countries. One of the ways which can be used by the Government of Indonesia is to confiscate the assets of the corruptors by claiming the assets obtained through a criminal act by means of what is called civil forfeiture in the countries practicing common law. Civil forfeiture was originally from England which was then developed in the United States which also practices the Principle of Common Law. This article describe about the corruption in the hadis maudu’, the classic are of Islam.